Animal cell technology : (Taylor & Francis Group, 2008)
The use of animal cells in medicine is over a century old, but it is in the past twenty years, with improved technology and the mapping of the human genome, that the possibilities and problems of creating biopharmaceuticals have become evident. A group of scientists, largely working in Brazil, present a comprehensive examination of the topic, including a roadmap of the cell with directions for cultivation and handling of the cells, and medical applications. They also discuss external factors such as quality control, government regulations and ethical debates. The volume is intended as a reference for scientists and medical researchers.